Next-generation sequencing in childhood disorders - Schnekenberg, R; Schnekenberg, R; Németh, A; Németh, A; Németh, A (2014)
Genetics has been revolutionised by recent technologies. The latest addition to these advances is next-generation sequencing, which is set to transform clinical diagnostics in every branch of medicine. In the research arena this has already been instrumental in identifying hundreds of novel genetic syndromes, making a molecular diagnosis possible for the first time in numerous refractory cases. However, the pace of change has left many clinicians bewildered by new terminology and the implications of next-generation sequencing for their clinical practice. The rapid developments have also left many diagnostic laboratories struggling to implement these new technologies with limited resources. This review explains the basic concepts of next-generation sequencing, gives examples of its role in clinically applied research and examines the challenges of its introduction into clinical practice.